Postharvest Aloe vera gel-coating modulates fruit ripening and quality of 'Arctic Snow' nectarine kept in ambient and cold storage - Ahmad, Muhammad; Singh, Zora; Khan, Ahmad (Institute of Food Science and Technology-John Wiley & Sons, 2009)
To evaluate the role of Aloe vera gel coating on ripening and fruit quality of nectarine (Prunus persica L. Batch cv 'Arctic Snow'), the uncoated and coated fruit were allowed to ripen at 20 ± 1 °C in first experiment and in the second experiment, the fruit were stored at 0 ± 0.5 °C and 90 ± 5% RH for 3 and 6 weeks prior to ripening at 20 ± 1 °C. Aloe vera gel-coated fruit kept at ambient or 3 and 6 weeks cold storage reduced respiration rate, ethylene production (62, 37 and 43% respectively), retarded fruit softening, reduced electrolyte leakage (EL), weight loss (65%), levels of ascorbic acid and total antioxidants (24, 9 and 13%) during ripening than control. In conclusion, Aloe vera gel can be used for extending storage life at ambient or cold storage and maintaining quality of 'Arctic Snow' nectarine.